2024
DOI: 10.1002/ctm2.1567
|View full text |Cite
|
Sign up to set email alerts
|

Dormant cancer cells and polyploid giant cancer cells: The roots of cancer recurrence and metastasis

Yuqi Jiao,
Yongjun Yu,
Minying Zheng
et al.

Abstract: Tumour cell dormancy is critical for metastasis and resistance to chemoradiotherapy. Polyploid giant cancer cells (PGCCs) with giant or multiple nuclei and high DNA content have the properties of cancer stem cell and single PGCCs can individually generate tumours in immunodeficient mice. PGCCs represent a dormant form of cancer cells that survive harsh tumour conditions and contribute to tumour recurrence. Hypoxic mimics, chemotherapeutics, radiation and cytotoxic traditional Chinese medicines can induce PGCCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 204 publications
0
1
0
Order By: Relevance
“…PGCCs play a detrimental role in cancer dormancy and reactivation, leading to disease recurrence. PGCCs enter dormancy through aberrant cell cycles mediated by P53 and CDK inhibitors and can exit dormancy by producing daughter cells ( Jiao et al, 2024 ). A recent study by Zheng et al found that after CoCl 2 treatment, the expression of Cdc42 and PAK1 increased, promoting the nuclear expression of phosphorylated stathmin (STMN1).…”
Section: Therapies Targeting Pgccsmentioning
confidence: 99%
“…PGCCs play a detrimental role in cancer dormancy and reactivation, leading to disease recurrence. PGCCs enter dormancy through aberrant cell cycles mediated by P53 and CDK inhibitors and can exit dormancy by producing daughter cells ( Jiao et al, 2024 ). A recent study by Zheng et al found that after CoCl 2 treatment, the expression of Cdc42 and PAK1 increased, promoting the nuclear expression of phosphorylated stathmin (STMN1).…”
Section: Therapies Targeting Pgccsmentioning
confidence: 99%